Financial accounting an introduction - Peirson, Graham; Ramsay, Alan (Addison Wesley Longman Australia Pty Limited, 1998)
It integrates the conceptual framework into an introductory accounting context and also ensures students develop a practical understanding of the basic recording of transactions and events.